The pricing and procurement of antiretroviral drugs: an observational study of data from the Global Fund - Vasan Ashwin; Hoos David; Mukherjee Joia S; Farmer Paul E; Rosenfield Allan G; Perriëns Joseph H (Bulletin of the World Health Organization, 2006)
The Purchase price report released in August 2004 by the Global Fund to Fight AIDS, Tuberculosis, and Malaria (Global Fund) was the first publication of a significant amount of real transaction purchase data for antiretrovirals (ARVs). We did an observational study of the ARV transaction data in the Purchase price report to examine the procurement behaviour of principal recipients of Global Fund grants in developing countries. We found that, with a few exceptions for specific products (e.g. lamivudine) and regions (e.g. eastern Europe), prices in low-income countries were broadly consistent or lower than the lowest differential prices quoted by the research and development sector of the pharmaceutical industry. In lower middle-income countries, prices were more varied and in several instances (lopinavir/ritonavir, didanosine, and zidovudine/lamivudine) were very high compared with the per capita income of the country. In all low- and lower middle-income countries, ARV prices were still significantly high given limited local purchasing power and economic strength, thus reaffirming the need for donor support to achieve rapid scale-up of antiretroviral therapy. However, the price of ARVs will have to decrease to render scale-up financially sustainable for donors and eventually for governments themselves. An important first step in reducing prices will be to make available in the public domain as much ARV transaction data as possible to provide a factual basis for discussions on pricing. The price of ARVs has considerable implications for the sustainability of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) treatment in the developing world.